STRATEGY FOR ENHANCING PUBLIC TRUST THROUGH INSTAGRAM CONTENT AND PUBLIC RELATIONS INTERACTION AT PELINDO REGIONAL 1 - Riki Novianto; Farhan Indra (Journal Analytica Islamica, 2026)
The development of digital technology has transformed public relations practices, particularly through the use of social media as a means of communication between organizations and their publics. Instagram has become one of the platforms widely used by organizations to disseminate information, build institutional image, and establish closer relationships with society. In the context of public organizations and state-owned enterprises, public trust constitutes an important asset that must be developed and maintained through effective communication. This study aims to analyze strategies for enhancing public trust through Instagram content and public relations interactions at Pelindo Regional 1. The study employed a qualitative approach using a descriptive method. Data were collected through observations of Pelindo Regional 1’s official Instagram account, documentation of posts and public interactions, and interviews with individuals involved in managing the organization’s social media. Data were analyzed using the Miles, Huberman, and Saldaña model, which consists of data condensation, data display, and conclusion drawing. The findings reveal that strategies for increasing public trust were implemented through the presentation of informative, consistent, and transparent content, supported by responsive and dialogical public relations interactions. Instagram content functioned both as a medium for disseminating information and as a representation of organizational values, while public relations interactions served as a form of two-way communication that strengthened relationships between the organization and its publics. These findings demonstrate that the combination of high-quality content and effective interaction contributes to building public trust in Pelindo Regional 1.